CHEMICAL DETOXIFICATION OF AFB1 IN EXPERIMENTAL QUAILS USING COMMERCIALLY AVAILABLE TOXIN BINDERS - S. Mahmood; M. Younus; A. Aslam; A. A. Anjum; M. L. Sohail (Journal of Animal and Plant Sciences, 2017)
AFB1 causes public health hazards by affecting 25% of world's food crops. For optimum production performance from poultry, proper detoxification of AFB1 in feed is mandatory. This study was designed to analyze the chemical detoxification potential of four commercially available toxin binders (activated charcoal, kaolin, vitamin E and selenium, myco-AD) in experimental quails fed with AFB1 added diets. For this purpose, 360 quail birds (divided in 6 groups) were reared in experimental conditions. Positive and negative control groups were fed basal diet and basal diet with 0.5mg/kg AFB1, respectively. Treatment groups were fed 4 different experimental diets with 0.5 mg/kg of AFB1 contamination and chemical binders added according to recommended dose rate. Growth parameters (feed intake, body weight gain &feed conversion ratio), hematology (hemoglobin, hematocrit, erythrocyte sedimentation rate, total leukocyte count), immune response and histopathology of soft organs (liver, kidney, lungs) of all the experimental birds were weekly recorded for 6 weeks and results were analyzed by Repeated Measure of ANOVA and Duncan Multiple Range Test. Results showed significant reduction in all the deleterious effects of AFB1 in all the tested parameters during the course of study. All the toxin binders brought significant changes (P < 0.05) in tested parameters. The active ingredient of Myco AD (Hydrated sodium calcium aluminosilicate, HSCAS) and Vitamin E and selenium were found as better detoxifying agent among the toxin binders used in this study. This study reports the success of commercially available toxin binders as chemical detoxification agent for the quails, an emerging protein source in thickly populated developing countries.
Keywords: Detoxification; Histopathology; Toxin binders; Quails